Data-Driven on Resilient Network Security Against SYN Flood Attacks at PT PUSRI - Misinem, .; M. Syaiful Huda, Mubarok; Timur, Dalipurwanto; Tamsir, Ariyadi; Nurul Adha Oktarini, Saputri (INTI International University, 2024)
The PT PUSRI Information Technology Services Department plays a vital role in supporting operations and providing IT services across the company. To ensure secure internet access, robust security measures have been implemented, with firewall filtering as a key strategy. This study analyzes the effectiveness of firewall filtering in mitigating threats such as SYN flood attacks and unauthorized access by focusing on data-driven insights into traffic patterns and threat prevention. The firewall filtering system scrutinizes incoming TCP connections, manages critical ports (e.g., ports 22 and 80), filters IP address ranges, and continuously monitors suspicious network traffic patterns. Data analysis of network activity revealed a significant reduction in security incidents. By blocking illegitimate traffic and managing commonly targeted entry points, the system has minimized disruptions caused by SYN flood attacks and unauthorized access attempts. Filtering source IPs associated with malicious activities and analyzing traffic anomalies further strengthen network security. The results demonstrate increased network stability and enhanced operational efficiency at PT PUSRI, with data indicating fewer disruptions and threats. The department's ability to analyze traffic patterns has enabled proactive threat mitigation, contributing to a secure IT environment. This research highlights the strategic importance of integrating data analysis into firewall filtering to sustain and improve network security while supporting seamless operational activities.